Les Arithmétiques de Diophante : lecture historique et mathématique - Rāshid, Rushdī; Houzel, Christian (Scientia Graeco-Arabica ;, 2013)
Until recently, only six of thirteen books comprising Diophantus' Arithmetica were known to us. Four other books in an Arabic translation have been discovered recently. We can now understand the organization of this work and its long-lasting impact on mathematics. The present book offers the first historical and mathematical study of the work as it has survived in ten books.